Solubility and preferential solvation of sulfadiazine, sulfamerazine and sulfamethazine in propylene glycol + water mixtures at 298.15 K (2023)
The equilibrium solubility of sulfadiazine, sulfamerazine and sulfamethazine in propylene glycol (PG) + water binary mixtures was determined at 298.15 K